Local Anesthetics with Vasoconstrictors in Hypertensive Patients Undergoing Dental Extraction Procedures: A Serial Case Report - Okti Kusumastiwi, Rr. Pipiet (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Systemic absorption of vasoconstrictors and adverse cardiac effects are reasons for not using vasoconstrictors in hypertensive patients. However, several recent studies reported that the use of local anesthetics with vasoconstrictors in hypertensive patients doesn’t cause a statistically significant increase in blood pressure and heart rate. The objective of the study is to evaluate the preoperative, intraoperative and postoperative blood pressure, heart rate and peripheral oxygen saturation in hypertensive patient who undergoing dental extraction procedures with local anesthetics with vasoconstrictors. Case presentation: We reported three serial cases of male patients (40, 45, 47 years old) undergoing radixes lower posterior tooth extracted, with blood pressures 143/88mmHg, 140/86mmHg and 142/86 mmHg. The patient underwent extraction under infiltration local anesthetics with vasoconstrictors (epinephrine). All patient’s blood pressure increased 1-3 points intraoperative and decreased again postoperative. The patient's heart rate also increased 10-25 times per minute intraoperative. The decrease in oxygen saturation (2%) only occurred in one patient, intraoperative. Conclusion: The slight hemodynamic changes in these three patients indicate that the use of local anesthetics with vasoconstrictors in hypertensive patients undergoing dental extraction procedures is relatively safe.